1997
DOI: 10.5980/jpnjurol1989.88.557
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Renal Disease in Patients With Reflux Nephropathy

Abstract: Glomerular damage due to either reflux nephropathy or dysplasia may cause proteinuria. Proteinuria of 100 mg/day was significantly (p < 0.01) associated with 2 SD of glomerular hypertrophy on histology and clinical observation (suggesting hyperfiltration). Thereafter, a rapid increase in proteinuria followed by diastolic hypertension appears be significant for predicting ESRD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…When the eGFR exceeds 40–50 ml/min/1.73 m 2 nephropathy rarely progresses, but disease progression is invariable when function is worse. Nakashima et al similarly reported that an isotopic GFR less than 49 ml/min predicted decline to ESRF [24]. …”
Section: Discussionmentioning
confidence: 99%
“…When the eGFR exceeds 40–50 ml/min/1.73 m 2 nephropathy rarely progresses, but disease progression is invariable when function is worse. Nakashima et al similarly reported that an isotopic GFR less than 49 ml/min predicted decline to ESRF [24]. …”
Section: Discussionmentioning
confidence: 99%
“…It is clear from the literature on adults that the development of progressive renal failure in CAKUT is rare unless the GFR is below the range of 40-50 ml/min per 1.73 m 2 [9,[14][15][16]. From the paediatric literature poor outcome has long been associated with high creatinine level and low clearance rate at 1 year [17,18], but there is still a dearth of isotopic GFR data from children which one can correlate with long-term outcome [7].…”
Section: Discussionmentioning
confidence: 96%
“…In severe cases of VUR, recurrent pyelonephritis leads to parenchymal injury and fibrotic scarring of the kidney, known as reflux nephropathy (RN) [6–9]. Congenital reflux nephropathy has also been coined and refers to RN in the context of VUR with a congenital renal malformation, and is often observed in the absence of pyelonephritis.…”
Section: Clinical Spectrum Of Vur and Reflux Nephropathymentioning
confidence: 99%